The Role of Remittance-Induced Credit Expansion in a Short-Run Keynesian Macroeconomic Model - Rashid, Muhammad; Sharma, Basu (Journal of Comparative International Management)

(untitled) (Management Futures, 2017)
This paper introduces a remittance-induced credit expansion in a static Keynesian macroeconomic model. A credit expansion in the monetary sector results in lowering the equilibrium level of interest rates, which in turn stimulates interest-sensitive consumption and investment. Secondly, the paper introduces a direct effect of remittances on investment. With the two extensions in a static Keynesian model of remittances, the paper derives the equilibrium level of national income and shows the effects of interactions of remittances with the monetary sector on national income. The results of the paper are illustrated numerically.